(untitled) (Scripta : English Department Journal, 2026)
This study explores how a shadow teacher utilizes song-based learning to support the pronunciation development of a student with speech sound disorders in an inclusive classroom setting. A descriptive qualitative case study design was employed, with data gathered through semi-structured interviews, classroom observations, and teachers’ documents, analyzed through thematic analysis. Three themes were identified: the shadow teacher’s strategies in implementing song-based learning, the challenges encountered, and the students’ pronunciation development and progress. The findings reveal three principal strategies: aligning song selection with classroom material, applying non-corrective feedback during pronunciation modeling, and delivering input at a deliberate pace. Challenges, including pronunciation regression, limited English proficiency, word repetition patterns, and inconsistent attendance, accompanied the implementation. Despite these obstacles, the student demonstrated discernible progress in vocabulary retention and classroom engagement. These findings suggest that song-based learning, when implemented through an individualized, contextually responsive approach, holds considerable potential as a practical instructional strategy for students with speech-sound disorders in inclusive educational settings.